Induction of cytochrome P4501A and biliary metabolites of pyrene and phenanthrene in Aequidens metae under laboratory conditions (2018)
Oil toxicity is a subject of ongoing research and it is important to gain knowledge about baseline levels in order to evaluate the environmental risk assessments associate to oil pollution in aquatic environments and to determine possible adverse effects on aquatic organisms. The study of biomarkers is suggested as an appropriate strategy to study the sublethal effects of contaminants, providing an early indication of possible adverse effects on organisms. The aim of this study was to evaluated two biomarkers in a freshwater fish commonly known as luminosa (Aequidens metae) through acute exposure to pyrene and phenanthrene by intraperitoneal induction. The fish were exposed for 10 days to nominal concentrations of 1, 10 and 50 ppm of pyrene and phenanthrene. Fish were sampled three times during the exposure time. In each fish, liver and bile were collected and kept in -80 ºC until the analysis. The induction of cytochrome P450 in the liver was estimated by ethoxyresorufin-Odeethylase (EROD) activity and the determination of PAH metabolites in bile was measured. The hepatic EROD activity showed an increase and biliary metabolites of pyrene and phenanthrene showed decreasing levels after the first sampling time, indicating the biotransformation efficiency of PAHs. Fish exposed to the highest concentration of pyrene showed higher levels of pyrene metabolites in bile and higher CYP1A induction evidencing monotonic effect. These dose-response data can be used as useful contributions in assessing environmental risk with respect to effluent pollution from the oil industry in Colombia.